Rapid prototyping technology for cranioplasty: A case series - Ashish Thakur; Dushyant Chauhan; M Viswambaran; R K Yadav; Dhruv Sharma (Wolters Kluwer Medknow Publications, 2019)
Cranial vault defects may be acquired or congenital in origin. Rehabilitation of these patients often poses challenge to the operating team and prosthodontist. Polymethylmethacrylate is a commonly used alloplastic graft material which is used for the fabrication of cranial prosthesis. Nowadays, with the advancement in the bioengineering, custom-made template and cranial prosthesis can be made by rapid prototyping technology (RPT) by patient three-dimensional (3D) computed tomography (CT) scan images. This series of two cases explained two different techniques for the rehabilitation of the patient with frontotemporoparietal cranial defect. Case 1 had a history of cerebrovascular accident, followed by decompression craniotomy which led to frontotemporoparietal defect of the left side. This defect area was associated with the cerebrospinal fluid accumulation which made delineation of underlying bony margins difficult and interfered with conventional impression procedures. Case 2 had a road traffic accident which led to intracerebral hemorrhage followed by decompression craniotomy which resulted in frontotemporoparietal defect of the right side. The patient had a poor neuromuscular control which impedes with the upright posture of the head during impression making of the defect area. Therefore, these cases were planned to rehabilitate by RPT. In these techniques, the prosthesis was made using custom-made skull template produced by RPT, using the data of 3D-CT scan images. This technique resulted in the prosthesis with good esthetics and better fit of the prosthesis. The contours of the prosthesis were replicated in the same manner as compared to the contralateral side. RPT is an additive manufacturing technology which is now used in the field of dentistry too. This technique is easy to use; fabricate prosthesis with high precision is less time-consuming and has fewer chances of error.